(untitled) (Philological Studies, 2019)
This paper examines the critical reflections of Prličev translations of Homer’s Iliad into the artificial language, called by some scholars as “Slav coine”. Attention will be given on recommendation of the Prličev’s translation of the Iliad by Marko Balabanov, Lazar Jovchev and Petko Slaveikov as editors of the journal Chitalishte where the first book and part of the second book of the Iliad was published as well as to the extremely negative statements of Nesho Bonchev, Hristo Botev and Lyuben Karavelov and on the subsequent moderate critical points of view expressed by Konstantin Velichkov, Evtim Sprostranov and Alexander Teodorov- Balan. Hence, translation of the Iliad by Prličev in this research is seen as an expression of the ideas of Slavic intercultural understanding that are present not only in translations, but also in Prličev creative identity and oeuvre.